Effects of cadmium on oxidative stress and cell apoptosis in Drosophila melanogaster larvae - Yang, Pingping; Yang, Xingran; Sun, Liran; Han, Xiaobing; Xu, Lu; Gu, Wei; Zhang, Min (Scientific reports, 2022)
With the increase of human activities, cadmium (Cd) pollution has become a global environmental problem affecting biological metabolism in ecosystem. Cd has a very long half-life in humans and is excreted slowly in organs, which poses a serious threat to human health. In order to better understand the toxicity effects of cadmium, third instar larvae of Drosophila melanogaster (Canton-S strain) were exposed to different concentrations (1.125 mg/kg, 2.25 mg/kg, 4.5 mg/kg, and 9 mg/kg) of cadmium. Trypan blue staining showed that intestinal cell damage of Drosophila larvae increased and the comet assay indicated significantly more DNA damage in larvae exposed to high Cd concentrations. The nitroblue tetrazolium (NBT) experiments proved that content of reactive oxygen species (ROS) increased, which indicated Cd exposure could induce oxidative stress. In addition, the expression of mitochondrial adenine nucleotide transferase coding gene ( sesB and Ant2 ) and apoptosis related genes ( Debcl, hid, rpr, p53, Sce and Diap1 ) changed, which may lead to increased apoptosis. These findings confirmed the toxicity effects on oxidative stress and cell apoptosis in Drosophila larvae after early cadmium exposure, providing insights into understanding the effects of heavy metal stress in animal development.